THE EFFECT OF EDUCATIONAL SOFTWARE ON ACHIEVEMENT IN MATHEMATICS AND THE DEVELOPMENT OF MATHEMATICAL THINKING AMONG NINTH GRADE STUDENTS IN JORDAN - Mohammad Nawaf Hmadneh (Adisam Publisher, 2025)
The current study aimed at identifying the effect of an educational software on the achievement of ninth grade students in the analysis of algebraic expressions, and the development of mathematical thinking. It was randomly divided into two groups, the first was an experimental group, which amounted to (51) students, who studied using the educational software, and the second group was control, which amounted to (51) students who studied using the usual method. Two tests were applied and their psychometric properties were verified, and they were applied before and after. The study found that there were statistically significant differences in the achievement of ninth grade students in the analysis of algebraic expressions, the level of mathematical thinking between the control and experimental group due to the experimental group that studied using educational software. Study recommended that the Ministry of Education hold training courses for mathematics teachers regarding how to employ educational software in the educational process.